2019
DOI: 10.1097/mnh.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system in the arcuate nucleus controls resting metabolic rate

Abstract: Purpose of review: Obesity represents the primary challenge to improving cardiovascular health, and suppression of resting metabolic rate (RMR) is implicated in the maintenance of obesity. Increasing evidence supports a major role for the renin-angiotensin system (RAS) within the brain in the control of RMR. Recent findings: The angiotensin II (ANG) Agtr1a receptor co-localizes with the leptin receptor (Lepr) primarily within cells of the arcuate nucleus (ARC) of the hypothalamus that also express Agouti-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…This notion is supported by recent studies showing that although animals with diet-induced obesity (DIO) can restore body weight, insulin levels and leptin sensitivity to normal after being switched to a normal fat diet, BP, renal sympathetic nerve activity (RSNA) and the activity of central RAS and PICs remain high ( Prior et al, 2010 ; Maric et al, 2014 ). Genetic disruption of AT1-R in leptin-expressing or agouti-related peptide (AGRP)-expressing cells in the ARC abolishes the thermogenic increase in sympathetic nerve activity in response to leptin, HFD, and deoxycorticosterone acetate (DOCA)-salt ( Claflin et al, 2017 ; Deng and Grobe, 2019 ). In rabbits, three weeks of HFD feeding led to increased BP, heart rate (HR) and RSNA.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by recent studies showing that although animals with diet-induced obesity (DIO) can restore body weight, insulin levels and leptin sensitivity to normal after being switched to a normal fat diet, BP, renal sympathetic nerve activity (RSNA) and the activity of central RAS and PICs remain high ( Prior et al, 2010 ; Maric et al, 2014 ). Genetic disruption of AT1-R in leptin-expressing or agouti-related peptide (AGRP)-expressing cells in the ARC abolishes the thermogenic increase in sympathetic nerve activity in response to leptin, HFD, and deoxycorticosterone acetate (DOCA)-salt ( Claflin et al, 2017 ; Deng and Grobe, 2019 ). In rabbits, three weeks of HFD feeding led to increased BP, heart rate (HR) and RSNA.…”
Section: Introductionmentioning
confidence: 99%
“…Cells of the arcuate nucleus of the hypothalamus (ARC) colocalize the AngII receptor AT1a with the leptin receptor. This AT1 receptor is required for stimulation of thermogenic sympathetic nervous activity, regardless of changes in food intake or blood pressure [ 12 ]. This local hypothalamic system presents a divergent profile compared with the peripherical RAS system [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells of the arcuate nucleus (ARC) of the hypothalamus co-express the AngII receptor (AT1a) and the leptin receptor (Lepr). These cells are also required for the specific stimulation of thermogenic sympathetic nervous activity and the subset of changes in the resting metabolic rate but not for the inhibition of food intake, giving the hypothalamic RAS a relevant role in the control of the body’s energy balance [ 12 ]. Multiple physiological and environmental conditions, including diet, determine the proper functioning of this system.…”
Section: Introductionmentioning
confidence: 99%
“…These data showed that the AT 1a R isoform is expressed in the mouse hypothalamus and selectively in a subset of AgRP neurons expressing SSt3, with no expression of the AT 1b R isoform (Table 1) [68]. It has been hypothesized these SSt3 ARC AgRP neurons project to a unique but unknown set of secondorder neurons to modulate energy expenditure, whereas GABAergic ARC AgRP neurons project to the PVN to participate in the control of food intake and blood pressure [72]. * Data obtained from a recent in silico reanalysis of published RNA-seq cell-specific gene-expression data in hypothalami obtained from male and female C57BL/6N mice during postnatal days 14-28, prior to sexual maturation [68].…”
Section: Angiotensin II Pathwaysmentioning
confidence: 97%